1997
DOI: 10.1002/hep.510260230
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of perihepatic lymph nodes in relation to liver histology and viremia in patients with chronic hepatitis C

Abstract: Hepatitis C virus (HCV) infection is one of the most comInflammatory processes in organs frequently lead to hypermon causes of chronic hepatitis and cirrhosis. 1,2 HCV is an plasia of regional lymph nodes. In the present study, we inves-RNA virus that preferentially replicates in hepatocytes; howtigated whether lymph node enlargement within the hepatoever, mononuclear lymphocytes may serve as a possible exduodenal ligament may reflect the inflammatory activity trahepatic site for HCV replication.3-5 Kinetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
3
22

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 26 publications
9
81
3
22
Order By: Relevance
“…It might be that other factors required to create the appropriate milieu for a GC reaction are usually missing in the liver microenvironment. A potential compartment where HCV can activate B cells might be perihepatic lymph nodes, which are frequently enlarged in patients with chronic HCV infection, and this is directly related to viral replication and to the recruitment of inflammatory cells [28,[43][44][45].Although we did not find indication for affinity maturation and hence antigen selection in the B-cell follicles, the IgV H gene segment usage indicated that antigen-specific B cells are preferentially recruited into these structures. In all seven follicles analysed, there was a preferential usage of the VH1-69 segment among the cloned V H 1 family rearrangements.…”
contrasting
confidence: 56%
“…It might be that other factors required to create the appropriate milieu for a GC reaction are usually missing in the liver microenvironment. A potential compartment where HCV can activate B cells might be perihepatic lymph nodes, which are frequently enlarged in patients with chronic HCV infection, and this is directly related to viral replication and to the recruitment of inflammatory cells [28,[43][44][45].Although we did not find indication for affinity maturation and hence antigen selection in the B-cell follicles, the IgV H gene segment usage indicated that antigen-specific B cells are preferentially recruited into these structures. In all seven follicles analysed, there was a preferential usage of the VH1-69 segment among the cloned V H 1 family rearrangements.…”
contrasting
confidence: 56%
“…On the other hand, upper abdominal lymph nodes are often enlarged in chronically HCV-infected patients, particularly in patients with viremia, suggesting that an HCV-specific immune response occurs in the regional lymph nodes in those patients 19,20 as well as in patients with other types of acute and chronic hepatitis. 21 In most infectious diseases, activation, differentiation, and proliferation of B cells specific for certain antigens usually occur in the lymph follicles of secondary lymphoid organs such as the regional lymph nodes and the spleen.…”
mentioning
confidence: 99%
“…intraabdominal, lymphadenopathy in IM (9). In the case of viral or immune-mediated liver disease, enlargement of perihepatic (9,16), peripancreatic (17) or retroperitoneal (18) lymph nodes represents activity of regional inflammation and/or immune response of the host, such as viral replication within the liver, direct spread of the hepatic inflammatory process, or recruitment of infected lymphocytes and/or macrophages to draining lymph nodes (16,18). In the case of EBV infection, proliferation of lymphocytes and/or production of immunoglobulin may be added to the definition of lymphadenopathy because of the lymphotropic nature of EBV and its potent B-cell stimulating action (3).…”
Section: Discussionmentioning
confidence: 99%